Lean logistics : high-velocity logistics infrastructure and the C-5 Galaxy - Ramey, Timothy L., 1951- (Rand, 1999)
As part of a body of research defining and evaluating the concept of Lean Logistics for the U.S. Air Force, this report considers the effects on operation of the C-5 Galaxy airlift aircraft of radically reducing the time required to move and repair aircraft components. Lean Logistics updates Air Force logistics operations by applying technology and management innovations that have proven effective in the commercial world, are relevant to the central supply problems of the Air Force, and are affordable. The analysis in this study used Air Force data to drive simulations of C-5 logistics operations and considered peacetime flying programs. This study found that a high-velocity infrastructure would provide C-5 performance that is the same as or better than that provided by the current infrastructure across a wide range of conditions and circumstances. A high-velocity infrastructure would require only one-sixth the amount of inventory at one-third the cost of the current infrastructure to produce the same operational performance.